La gestión de calidad y la satisfacción al cliente en el GAD Municipal del cantón Chambo - Zabala Álvarez, María Alejandra (2024)
ABSTRACT: This research studies and examines customer satisfaction and quality management in the Autonomous Decentralized Government - GAD of the Chambo canton. Due to quality management is crucial to providing a service because it affects the satisfaction or dissatisfaction of users. Service and staff effectiveness are the two key dimensions of customer satisfaction that are considered holistically to ensure compliance. Thus, the quality of the service provided by the employees of the GAD Chambo is evaluated through interviews and surveys to determine the users' satisfaction level. To discover possible errors in the management model and correct them according to the users' needs. Quality management and customer satisfaction are considered the variables of interest in this research; they are related and develop strategies to improve the service. It was detected that, although the quality of the service had positive aspects, there were also areas for improvement, such as the need for more collaboration on the part of users and the slowness of service. In addition, users felt dissatisfaction due to the staff's lack of friendliness and the lack of additional attention points. Finally, plans were presented to improve quality management and customer satisfaction, such as an internal manual, an information socialization plan, a communication channel for complaints, and an information balcony. These strategies aim to improve service and ensure that clients of the Municipal GAD of the Chambo canton are satisfied. Keywords: Management, quality, satisfaction, customer, GAD.